Optimizing Cash Waqf for Financing Climate Change Mitigation: Opportunities and Challenges - Raniah, Thifal; Rohim, Ade Nur (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
Financing climate change mitigation requires large costs that each country must incur. Likewise, developing countries are more vulnerable to climate change. Cash waqf as an Islamic social financial instrument has the opportunity to become a supportive financing alternative. This research aims to provide a new paradigm in developing cash-waqf-based climate change mitigation programs. This research uses qualitative methods with data collection techniques through literature study and analysis using descriptive content analysis. Waqf and the environment are in line with the goal of maqashid sharia, namely human welfare. Innovations in financing climate change mitigation programs can be carried out through Cash Waqf Linked Sukuk (CWLS), Blue Waqf, and Green Waqf. Even though there is an opportunity for cash waqf to become alternative financing for cash waqf, there is still a need to create an ecosystem that supports the running of climate change mitigation programs on a cash waqf basis. Improvements are needed from various related parties to increase the quality and awareness of cash waqf and climate change mitigation.